A framework for evaluating the European airline costs of disabled persons and persons with reduced mobility. (January 2016) - Ancell, Deborah; Graham, Anne
Abstract: In recent years, airlines have been servicing a greater variety, and increasing numbers, of disabled persons and persons with reduced mobility (PRMs), particularly associated with ageing, obesity and medical needs. With the quantity of PRMs likely to increase in the future, there will be a growing impact on the airlines' associated actual and opportunity costs, about which there is minimal literature and data. Therefore the aim of this paper is to identify standard functional key factors (FKFs) with which airlines could audit their PRMs costs, and which could be used by other interested bodies, such as governments, when considering relevant aviation policy. These FKFs are related to nine areas, namely PRMs' transfers; mobility aids; aircraft delays/diversions costs; staff training costs; staff health, safety and welfare; aircraft fixtures and equipment costs; airport costs; transaction costs; and opportunity costs. Further research is needed to obtain the data for these FKFs. Highlights: The number of disabled persons and persons with reduced mobility (PRMs) flying by air are likely to increase with population ageing, obesity and medical tourism. Airlines incur actual and opportunity costs related to PRMs. Functional key factors (FKFs) are used to identify these costs.